2003
DOI: 10.1590/s0100-879x2003000400018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypertonic sodium chloride solution on the electrophysiologic alterations caused by bupivacaine in the dog heart

Abstract: The effects of various hypertonic solutions on the intraventricular conduction, ventricular repolarization and the arrhythmias caused by the intravenous (iv) injection of bupivacaine (6.5 mg/kg) were studied in sodium pentobarbital-anesthetized mongrel dogs. Hypertonic solutions, given iv 5 min before bupivacaine, were 7.5% (w/v) NaCl, 5.4% (w/v) LiCl, 50% (w/v) glucose (2,400 mOsm/l, 5 ml/kg), or 20% (w/v) mannitol (1,200 mOsm/l, 10 ml/kg). Bupivacaine induced severe arrhythmias and ventricular conduction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…..................................................................................................................................................................................................................... Ó 2010 The Authors blockers at their binding sites [10][11][12]. Previous investigators exploring hypertonic saline solutions in bupivacaine cardiotoxicity have demonstrated that 7.5% sodium chloride prevents the detrimental effects of bupivacaine on cardiac stimulus conduction and ventricular repolarisation in whole dogs, independent of hypertonicity alone [13]. This work proposes reversal, at least in part, of the bupivacaine-induced sodium channel blockade as the principal beneficial mechanism of action of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…..................................................................................................................................................................................................................... Ó 2010 The Authors blockers at their binding sites [10][11][12]. Previous investigators exploring hypertonic saline solutions in bupivacaine cardiotoxicity have demonstrated that 7.5% sodium chloride prevents the detrimental effects of bupivacaine on cardiac stimulus conduction and ventricular repolarisation in whole dogs, independent of hypertonicity alone [13]. This work proposes reversal, at least in part, of the bupivacaine-induced sodium channel blockade as the principal beneficial mechanism of action of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose insulin dextrose euglycaemia has been shown to exert a positive inotropic action in bupivacaineinduced myocardial depression, perhaps via an antagonistic influence of insulin on sodium channel inhibition, transient outward potassium current, calcium-dependent adenosine triphosphatase, or even improved myocardial glucose utilisation [9]. Hypertonic saline solutions have been shown to reverse the cardiodepressant and arrhythmogenic effects of bupivacaine intoxication both in vitro [10] and in vivo [11][12][13]. Given the differing mechanisms of action between these unique therapies and lipid emulsion, largely pharmacodynamic in the case of the former and pharmacokinetic in the latter, potential exists at least theoretically for any combined effect to be cumulative.…”
mentioning
confidence: 99%